(untitled) (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
Web3 promised to give users control over their digital identity. Five years in, the reality is messier. Most dApp users still authenticate with a bare Ethereum address – a 42-character hex string with no name, no reputation, no credentials, and no recovery mechanism if the private key is lost. The decentralised identity stack that was supposed to fix this – DIDs, verifiable credentials, ENS names, soulbound tokens, and zero-knowledge proofs of personhood – exists in fragments that do not interoperate. We present the Web3 Identity Management Assessment Framework (W3IMAF), a systematic evaluation of six decentralised identity approaches – ENS-style naming, DID-based self-sovereign identity, soulbound token reputation, zero-knowledge credential proving, social recovery wallets, and cross-chain identity aggregation – tested on a unified identity testbed that measures resolution latency, credential verification speed, privacy preservation, GDPR compliance, recovery robustness, and cross-platform portability. Our Identity Quality Score (IQS) shows that DID-based SSI with ZK credential proofs achieves the highest overall quality (0.908) but social recovery wallets solve the most urgent practical problem – key loss, which causes an estimated USD 4-6 billion in permanently inaccessible crypto assets annually.